Teacher-student interactions for enhanced learning in upper secondary mathematics classroom - Aline Dorimana; Alphonse Uworwabayeho; Gabriel Nizeyimana (Institute of Advanced Engineering and Science, 2022)
Interactive teaching practices in mathematics classrooms are encouraged to meet the learning potential. However, how it is applied in the classroom is still challenging. This paper uses evidence gathered from a large research project to contribute to the understanding of teacher-student interactions. It followed an interventional approach with two teachers and 82 students of two grade 11 classes from one school of Kayonza District in Rwanda. Data were collected through observations, video recordings, and field notes. Results revealed that there is a variety of ways to facilitate and keep interactive learning. These include asking purposeful questions and giving feedback. The quality of teacher facilitation (52%) and students' engagement (60%) were moderately high. However, there was little guidance from teachers in the problem-solving process and the classroom discourse. It is argued that the role of instructional language in communication hinders the quality of teacher-student interactions. This leads us to advise an exploration of language supportive pedagogy in the Rwandan context.